Chlorhexidine and povidone-iodine: Unmasking the unknown in catheter-related infection prevention, a narrative review - Bertrand Drugeon; Claire M. Rickard; Jessica A. Schults; Jérémy Guenezan; Olivier Mimoz (Journal of Infection and Public Health)
Healthcare-associated infections remain a major concern, with vascular access devices contributing substantially to infection risk. Effective skin disinfection is essential for preventing catheter-related infections (CRIs). This narrative review compares the efficacy and safety of chlorhexidine gluconate (CHG) and povidone-iodine (PVI), while also addressing often-underexamined factors such as product availability, application techniques, antimicrobial resistance and environmental impact. Evidence supports the use of 2 % CHG in 70 % isopropyl alcohol as the most effective strategy to reduce CRIs, although PVI remains an alternative in patients with CHG intolerance or in low-resource settings. Environmental analyses highlight the higher persistence and potential ecological risk of CHG compared with PVI. Despite widespread guidelines, significant discrepancies persist in recommended concentrations, application methods, and target populations. Based on literature synthesis, we propose standardising the use of 2 % CHG-IPA where feasible, developing tailored recommendations for high-risk groups, and incorporating environmental and economic considerations into future infection prevention strategies.